Effect of methyl jasmonate on in-vitro pollen germination and tube elongation ofPinus nigra - ÇETİNBAŞ GENÇ, ASLIHAN; VARDAR, FİLİZ (SPRINGER WIEN, 2020)
The purpose of the main research was to investigate the effects of methyl jasmonate (MeJA) (0.05, 0.25, 0.5, and 2.5 mM) on the pollen germination and tube elongation ofPinus nigra. Total pollen germination rate increased after MeJA treatments while the most enhancement was observed at 0.05-mM MeJA. No germination was observed at 2.5-mM MeJA. Although the unipolar and bipolar germination were observed in all groups, no significant changes were observed in unipolar and bipolar pollen germination rates after MeJA treatments. Tube length increased only at 0.05-mM MeJA. Although branched tubes were observed in all groups, branched tube rate increased only at 0.05-mM MeJA. Although two branched, three branched, and consecutive branched tubes were observed in all groups, the most common branching type was two branched type in all groups. Although anisotropy of actin filaments in the shank and apex of unbranched tubes decreased after MeJA treatments, the most decrease was observed at 0.05-mM MeJA. Also, anisotropy of actin filaments in the shank and in pre-branching region of branched tubes decreased only at 0.25-mM MeJA. Anisotropy of both two apexes of a branched tube changed only at 0.25- and 0.5-mM MeJA. Callose accumulation in the apex of unbranched and branched tubes increased in parallel with the increase in MeJA concentration. However, more callose is accumulated in one apex than the other apex of a branched tube. In conclusion, MeJA affected the actin organization, changed the callose distribution, and altered the pollen tube growth ofPinus nigra.
Keywords: Actin cytoskeleton; Bipolar germination; Cell wall; Gymnosperm; Methyl jasmonate; Pollen tube; ACTIN-FILAMENT ORGANIZATION; CELL-WALL CONSTRUCTION; ETHYLENE PROMOTES; SUCROSE SYNTHASE; PINUS-BUNGEANA; STRESS AFFECTS; GROWTH; CYTOSKELETON; ACCUMULATION; MICROTUBULE